Kapasitas Terminal Penumpang Domestik di Bandar Udara Internasional Adi Soermarmo Boyolali - Ristiani Ristiani; Esti Nur Wakhidah; Iman Rahmad Prayoga (Institut Transportasi dan Logistik Trisakti, 2021)
This research aimed to analyze the capacity of domestic passenger terminal in Adi Soemarmo Boyolali International Airport. The data were collected from observation, documents, and literature review and analyzed using the formula in the Regulation of the Minister of Transportation of the Republic of Indonesia No. PM 178 of 2015 on Service Standards for Airport Service User. The capacity of the terminal in this airport was used as an initial forecast of the needs for facility development, including area per during peak hour passenger and Initial Indication of Development, Utilization, Expansion, and Operation (abbreviated as IAP4 in Indonesian). Based on the calculation, the IAP4 value of the terminal was 0.32, indicating the capacity was sufficient. In 2019, as there were 1,565,093 passengers departing domestically from this terminal, the peak hour passenger coefficient was 0.050. Based on these findings, the existing capacity of the domestic terminal was sufficient to accommodate up to 2,925,600 passengers. Therefore, the terminal’s level of occupancy was 53.49% in 2019. It is necessary to carry out this research regularly, particularly when there is an increase in the number of passengers to evaluate whether the airport is still able to accommodate all passengers’ movements.